A modified rare earth oxide-supported cobalt-based catalyst for hydrogen production by decomposing ammonia and a preparation method thereof

The preparation of yttrium oxide-supported cobalt or nickel catalysts through the surfactant template method and the impregnation method has solved the problems of high cost, poor stability and low activity of existing catalysts, and achieved efficient and stable ammonia decomposition and hydrogen production effect, which is suitable for large-scale applications.

CN118527147BActive Publication Date: 2025-04-04HUIZHOU INSTITUTE OF GREEN ENERGY & ADVANCED MATERIALS +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410415965.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-08
Publication Date
2025-04-04
Estimated Expiration
2044-04-08

AI Technical Summary

Technical Problem

The existing catalysts have high synthesis costs, poor thermal stability and low catalytic activity in the hydrogen production process of ammonia decomposition, which is difficult to meet the needs of large-scale applications.

Method used

A yttrium oxide-supported cobalt or nickel catalyst is prepared by the surfactant template method, and the transition metal element cobalt or nickel is supported on the yttrium oxide support by impregnation method to form a catalyst with high specific surface area and high catalytic activity.

Benefits of technology

The high specific surface area and high catalytic activity of the catalyst are achieved, the preparation cost is reduced, the ammonia conversion rate and thermal stability are improved, and it is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004780817640000071
    Figure BDA0004780817640000071
  • Figure BDA0004780817640000072
    Figure BDA0004780817640000072
  • Figure BDA0004780817640000081
    Figure BDA0004780817640000081
Patent Text Reader

Abstract

The present invention provides a modified rare earth oxide-supported cobalt-based catalyst for ammonia decomposition to produce hydrogen and a preparation method thereof. The cobalt-based modified rare earth oxide catalyst provided by the present invention is prepared by the following steps: (1) mixing a nitrate containing rare earth elements, transition elements, etc. with a surfactant solution, adding an organic amine for complexation, filtering, drying, and roasting to obtain a carrier; (2) loading cobalt onto the above-synthesized carrier by an impregnation method to obtain a modified rare earth oxide-supported cobalt-based catalyst. The catalyst prepared by the method of the present invention has a relatively simple preparation method and low preparation cost, and can better overcome the problem of low catalytic activity in the existing process, and can be used in the production of catalytic ammonia decomposition to produce hydrogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a modified rare earth oxide-supported cobalt-based catalyst for hydrogen production by decomposing ammonia and a preparation method thereof. Background Art

[0002] Hydrogen is the simplest atom of all molecules and is a material that has successfully completed many historical missions: it powers the engines of space rockets and plays a role in the steel industry and the electronics manufacturing industry. However, hydrogen often encounters problems with hydrogen storage during use: ① There is no infrastructure dedicated to transporting hydrogen energy; ② There are safety issues with vehicles or ships storing hydrogen; ③ There is no direct hydrogen energy source. Therefore, it is necessary to find a suitable hydrogen energy carrier that can generate high energy when used and has no safety issues. Since the hydrogen storage capacity of ammonia is 17.6wt%, the hydrogen storage capacity is 124g·L -1 , can be liquefied at room temperature and a medium pressure of about 8 bar, with an energy density of 4.25 kWh·L -1 ,Ammonia is gaining more and more attention as a hydrogen storage energy carrier because it is easier to store and transport, and only emits water and nitrogen through complete combustion, without causing secondary pollution.

[0003] The decomposition of ammonia to produce hydrogen generally requires catalysis by a catalyst. However, the existing catalysts have high synthesis costs, poor thermal stability, and average activity performance. CN112774676B discloses a method for preparing a rare earth oxide-supported ruthenium catalyst. Although the catalyst reported in the patent has strong catalytic activity for ammonia decomposition, its preparation method is complicated and uses a high content of precious metal ruthenium. The literature (Chen-Feng Cao, et al. Chemical Engineering Science 257 (2022 117719) reported that ruthenium (Ru) nanoparticles supported on LaAlO3 (a typical ABO3 perovskite oxide) were used as an effective catalyst for ammonia decomposition. The results show that Ru / La 0.8 Sr 0.2 AlO3 catalyst has a higher hydrogen production rate and lower activation energy. cat -1 h -1 At 500 °C, the hydrogen production rate is 941 mmol / g Ru -1 min -1 , the conversion rate of ammonia is 71.6%. Although patents and literature have shown the high activity of Ru-based catalysts, the high price and limited reserves of Ru have restricted its large-scale application in the future.

[0004] The literature (Hiroki Muroyama, et al. Applied Catalysis A: General 443–444 (2012) 119–124) prepared various nickel catalysts loaded with metal oxides and studied their catalytic activity for ammonia decomposition. When the nickel loading of the Ni / La2O3 catalyst varied in the range of 10-70wt%, the sample containing 40wt% Ni showed the highest conversion at 550°C, which was 78.9% (GHSV = 6,000mLg cat -1 h -1 ), it can be seen that the disclosed non-precious metal catalysts have poor activity.

[0005] In summary, providing a low-temperature, high-activity, high-stability, low-cost non-precious metal catalyst is of great significance and is a problem that needs to be urgently solved by those skilled in the art. Summary of the invention

[0006] In order to solve the above problems, the first purpose of the present invention is to provide a method for preparing the above-mentioned yttrium oxide-loaded cobalt-based catalyst, wherein a surfactant template method is used to prepare an yttrium oxide carrier, and cobalt is loaded on the yttrium oxide carrier by an impregnation method to prepare an yttrium oxide-loaded cobalt-based catalyst, which has the advantages of large catalyst specific surface area and high catalytic activity.

[0007] The second purpose of the present invention is to provide a method for preparing the above-mentioned other yttrium oxide-loaded nickel-based catalyst, wherein the yttrium oxide-metal oxide carrier is prepared by a surfactant template method, and cobalt is loaded on the yttrium oxide-metal oxide carrier by an impregnation method to prepare the catalyst. Since non-precious metals are used to synthesize the catalyst, the preparation cost is greatly reduced and it is expected to be applied on a large scale.

[0008] The third object of the present invention is to provide a catalyst prepared by the above method for use in ammonia decomposition to produce hydrogen, which has the advantages of high pure ammonia conversion rate and good stability, and overcomes the shortcomings of existing catalysts such as low ammonia conversion rate and poor thermal stability.

[0009] In order to achieve the above first purpose, the technical solution adopted by the present invention is: a rare earth oxide yttrium oxide supported cobalt-based catalyst, which comprises the following components by mass percentage:

[0010] 1) Y2O3 carrier 80-95%, the specific surface area of ​​Y2O3 carrier is 55m 2 / g~80m 2 / g,

[0011] 2) Transition metal element cobalt 5-20%;

[0012] Alternatively, the following components are included in percentage by mass:

[0013] 1) Y2O3-M y O x Carrier 70-95%, M is other metal elements, Y2O3-M y O x The specific surface area of ​​the carrier is 34m 2 / g~89m 2 / g;

[0014] 2) Transition metal element cobalt 5-30%.

[0015] It can be seen from the above technical solution that the specific surface area of ​​the catalyst carrier provided by the present invention can reach up to 80m 2 / g.

[0016] In a further embodiment, M is one of the elements selected from the group consisting of magnesium, lanthanum, zinc, zirconium, aluminum, cerium, iron, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, erbium, thulium, ytterbium, lutetium, and scandium.

[0017] In order to achieve the above first purpose, the technical solution adopted by the present invention is: a method for preparing a rare earth oxide yttrium oxide supported cobalt-based catalyst, comprising the following steps:

[0018] 1) dissolving one or more of a surfactant polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), coconut oil diethanolamide (6501), polyoxyethylene ether of isomeric decanol, and fatty alcohol polyoxyethylene ether (AEO-3) in deionized water, and then adding Y(NO3)3.6H2O under stirring to obtain a mixed solution A;

[0019] 2) slowly adding an organic amine (one of diethylamine, triethylamine, triethanolamine, and tetrabutylammonium bromide) dropwise to the mixed solution A obtained in step 1), then continuing to stir, and aging in a water bath, and filtering while hot to obtain a white precipitate;

[0020] 3) washing the white precipitate obtained in step 2) with deionized water until the filtrate is neutral, drying the white precipitate, and then calcining to obtain a Y2O3 carrier;

[0021] 4) dissolving a certain amount of Co(NO3)2.6H2O in an appropriate amount of organic solution containing hydroxyl or carbonyl groups, and then impregnating it on a Y2O3 carrier. After drying, the dried product is calcined in an air atmosphere to obtain a catalyst precursor Co / Y2O3;

[0022] It can be seen from the above technical scheme that the surfactant in step 1) has the function of reducing interfacial tension, facilitating emulsification, dispersion and stabilization of liquid particles, and may increase the specific surface area of ​​the carrier; the addition of organic amine in step 2) makes Y 3+The precipitation is then washed to neutrality to remove OH. -1 , calcining to remove carbon and water in the carrier to obtain a Y2O3 carrier; step 4) impregnating cobalt on the carrier by an impregnation method. Experiments show that the specific surface area of ​​the catalyst prepared by the present invention can be as high as 55m 2 / g to 80m 2 / g, the catalytic activity of the catalyst is greatly enhanced.

[0023] A further scheme is that in step 1), the amount of surfactant is 5 to 10 mmol, the amount of Y(NO3)3.6H2O is 5 to 15 mmol, and the amount of deionized water is 100 to 200 mL; in step 2), an organic amine is added to the mixed solution A and the stirring time is continued for 5 to 12 hours, the temperature of the water bath heating is 50 to 100°C, and the aging time is 6 to 24 hours; in step 3), the drying temperature is 110 to 120°C, the drying time is 6 to 9 hours, and the calcination temperature range is 500°C; in step 4), the organic solution containing hydroxyl or carbonyl groups is one of anhydrous ethanol, anhydrous methanol or anhydrous acetone, the drying temperature is 60 to 120°C, and the calcination temperature is 500 to 1000°C.

[0024] In order to achieve the above second object, the technical solution adopted by the present invention is: a method for preparing a modified yttrium oxide-supported cobalt-based catalyst, characterized in that it comprises the following steps:

[0025] 1) dissolving one or more of a surfactant polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), coconut oil diethanolamide (6501), polyoxyethylene ether of isomeric decanol, and fatty alcohol polyoxyethylene ether (AEO-3) in deionized water, and then adding Y(NO3)3.6H2O and metal salt N under stirring to obtain a mixed solution B;

[0026] 2) slowly adding an organic amine (one of diethylamine, triethylamine, triethanolamine, and tetrabutylammonium bromide) dropwise to the mixed solution B obtained in step 1), then continuing to stir, aging in a water bath, and filtering while hot to obtain a precipitate;

[0027] 3) The precipitate obtained in step 2) is washed with deionized water until the filtrate is neutral, and then the white precipitate is dried and then calcined to obtain Y2O3-M y O x Carrier;

[0028] 4) Dissolve a certain amount of Co(NO3)2.6H2O in an appropriate amount of organic solution containing hydroxyl or carbonyl groups, and then immerse it into the above Y2O3-M y O xThe carrier was then transferred to a forced air drying oven for drying, and the dried product was calcined in an air atmosphere to obtain the catalyst Co / Y2O3-M y O x ;

[0029] A further scheme is that in step 1), the amount of the surfactant is 5 to 10 mmol, the amount of Y(NO3)3.6H2O is 3 to 9 mmol, and Y(NO3)3.6H2O is reacted with a metal salt N (N is one of magnesium nitrate pentahydrate, lanthanum nitrate hexahydrate, zinc acetate, zirconium nitrate hexahydrate, aluminum nitrate nonahydrate, iron nitrate nonahydrate, cerium nitrate hexahydrate, praseodymium nitrate hexahydrate, neodymium nitrate hexahydrate, promethium nitrate hexahydrate, samarium nitrate hexahydrate, europium nitrate hexahydrate, gadolinium nitrate hexahydrate, terbium nitrate hexahydrate, erbium nitrate hexahydrate, thulium nitrate hexahydrate, ytterbium nitrate hexahydrate, lutetium nitrate hexahydrate, and scandium nitrate hexahydrate) The molar ratio of the metal elements in the step is 1:1 to 1:9, and the amount of deionized water is 100 to 200 mL; in step 2), an organic amine is added to the mixed solution A and the stirring time is continued for 5 to 12 hours, the temperature of the water bath heating is 60 to 120° C., and the aging time is 12 to 24 hours; in step 3), the drying temperature is 60 to 120° C., the drying time is 8 to 18 hours, and the calcination temperature is 300 to 900° C.; in step 4), the organic solution containing hydroxyl or carbonyl groups is one of anhydrous ethanol, anhydrous methanol or anhydrous acetone, the drying temperature is 60 to 180° C., and the catalyst is calcined in a muffle furnace at a temperature of 300 to 1000° C.

[0030] Experiments show that the specific surface area of ​​the modified catalyst prepared by the present invention can reach up to 90m 2 / g.

[0031] In order to achieve the third purpose, the technical solution adopted by the present invention is: the yttrium oxide supported cobalt-based catalyst of the present invention is used for the decomposition of ammonia to produce hydrogen, with pure ammonia as the raw material, at a reaction temperature of 300-600°C, a reaction pressure of normal pressure (±0.01MPa), and a weight space velocity of 6000-30000mLh -1 g cat -1 The catalyst is contacted with the catalyst bed under the conditions of (in the reaction furnace, the catalyst needs to be reduced with hydrogen before contacting with ammonia, and the hydrogen reduction temperature is in the range of 500-700°C), and the reaction generates a product containing hydrogen.

[0032] The catalyst prepared by the preparation method of the present invention is used in the field of hydrogen production by decomposing ammonia, which reduces the preparation cost and improves the raw material conversion rate. DETAILED DESCRIPTION

[0033] [Example 1]

[0034] Preparation method of yttrium oxide supported cobalt-based catalyst:

[0035] 1. Dissolve 4 g of surfactant in a beaker filled with 150 mL of deionized water, add a clean magnetic stirrer to the beaker, place the beaker on a magnetic stirrer, and add 4.2319 g of Y(NO3)3·6H2O under constant stirring to obtain a mixed solution A.

[0036] 2. Three hours later, organic amine was slowly added to the mixed solution A obtained in step 1, and stirring was continued until the pH of the solution reached 10. Stirring was then continued for 4 hours, and the mixture was aged in a 90° C. water bath for 3 hours. The mixture was filtered while hot to obtain a white precipitate.

[0037] 3. Filter and wash the white precipitate obtained in step 2 with deionized water until the filtrate is neutral, then put the white precipitate into a 70°C oven and dry it for 12 hours. Then put the dried precipitate into a muffle furnace, control the muffle furnace to heat up to 400°C at a heating rate of 5°C / min, and then calcine for 2 hours to obtain a Y2O3 carrier.

[0038] 4. Use an electronic analytical balance to weigh 0.8000g of the above-mentioned Y2O3 carrier and 0.4390g of Co(NO3)2·6H2O respectively, add Co(NO3)2·6H2O and 15mL of deionized water into a beaker (capacity 100mL), stir until Co(NO3)2·6H2O is dissolved, put a clean magnetic stirring bar and the weighed Y2O3 carrier into the beaker, place the beaker on a magnetic stirrer and stir for 3h, then put it into a 60℃ forced drying oven and dry it for 12h, then put the dried product into a muffle furnace, and calcine it at 600℃ for 2h in an air atmosphere at a heating rate of 5℃ / min to obtain the catalyst Co / Y2O3.

[0039] [Example 2-5]

[0040] Y(NO3)3.6H2O, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and triethylamine (TEA) are prepared according to the conditions in Table 1 and the steps in Example 1 to obtain the Co / Y2O3 catalysts of Examples 2-5.

[0041] Table 1

[0042]

[0043] [Examples 6-10] Cobalt-based catalysts are used to decompose ammonia to produce hydrogen.

[0044] Using ammonia as raw material and the Co / Y2O3 catalyst obtained in Examples 1-5, the catalyst performance was evaluated according to the reaction conditions in Table 2.

[0045] Table 2

[0046]

[0047]

[0048] Conclusion: From Table 1 and Table 2, it can be seen that at an air velocity of 6000mLg cat -1 h -1 When the catalyst obtained in Example 1 has the largest specific surface area and the best catalytic performance, the reaction temperature is 300-600° C. and the reaction is under normal pressure, the ammonia decomposition conversion rate can reach 95%.

[0049] [Example 11]

[0050] Preparation method of modified Co / Y2O3 catalyst:

[0051] 1. Dissolve 4 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) in a beaker filled with 200 mL of deionized water, add a clean magnetic stir bar to the beaker, place the beaker on a magnetic stirrer, and add 1.9652 g of Y(NO3)3·6H2O and 2.1648 g of La(NO3)3·6H2O under constant stirring to obtain a mixed solution B;

[0052] 2. After one hour, triethylamine (TEA) was slowly added to the mixed solution B obtained in step 1, and the mixture was stirred continuously until the pH value of the solution reached 10. The mixture was then stirred for 4 hours, and aged in a water bath at 90° C. for 3 hours. The mixture was filtered while hot to obtain a white precipitate.

[0053] 3. Filter and wash the white precipitate obtained in step 2 with deionized water until the filtrate is neutral, then put the white precipitate into a 70°C oven and dry it for 12 hours, then put the dried precipitate into a muffle furnace, control the muffle furnace to heat up to 500°C at a heating rate of 5°C / min, and then calcine for 2 hours to obtain a Y2O3-La2O3 carrier, recorded as Y-La;

[0054] 4. Use an electronic balance to weigh 0.8000g of the above-mentioned carrier and 0.9878g of Co(NO3)2·6H2O respectively, add the weighed Co(NO3)2·6H2O and 15mL of deionized water into a beaker (capacity 100mL), stir until Co(NO3)2·6H2O is dissolved, put a clean magnetic stirring bar and the weighed Y2O3-La2O3 carrier into the beaker, place the beaker on a magnetic stirrer and stir for 3h, then put it into a 60℃ forced drying oven and dry it for 12h, then put the dried product into a muffle furnace, and calcine it at 600℃ for 2h in an air atmosphere at a heating rate of 5℃ / min to obtain the catalyst Co / Y-La.

[0055] The obtained catalyst contains 80% Y-La mixed oxide carrier, the content of metal cobalt as the active component in the catalyst accounts for 20% by weight, and the specific surface area of ​​the catalyst is 44m 2 / g.

[0056] [Examples 12-19]

[0057] Y(NO3)3·6H2O, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), triethylamine (TEA) and nitrate compound raw materials containing the elements magnesium, lanthanum, zinc, zirconium, aluminum, cerium, iron, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, erbium, thulium, ytterbium, lutetium and scandium are prepared according to the preparation conditions in Table 3 and the steps in Example 11 to obtain the modified catalysts of Examples 12-19.

[0058] Table 3

[0059]

[0060]

[0061] Conclusion: A series of carriers can be obtained according to the conditions in the table. These carriers are modified by adding different metal nitrates. A series of magnesium-modified yttrium oxide carriers with different molar ratios of yttrium and lanthanum are also prepared. Subsequent catalytic activity tests show that the lanthanum-modified yttrium oxide carrier has a significant improvement in catalytic activity, among which the carrier with a molar ratio of lanthanum to yttrium metal equal to 1 is the best.

[0062] [Examples 20-28] Using modified catalysts to produce hydrogen by decomposing ammonia

[0063] Using ammonia as raw material and the modified catalysts obtained in Examples 11-19, the catalyst performance was evaluated according to the reaction conditions in Table 4.

[0064] Table 4

[0065]

[0066]

[0067] Conclusion: From the table, we can see that at an air velocity of 12,000 mLg at -1 h -1 When the reaction temperature is in the range of 300-600℃, a series of metal-modified Co / Y2O3-M y O x Among the catalysts, the lanthanum-modified catalyst achieved good ammonia decomposition conversion rate, among which the catalyst with a yttrium to lanthanum molar ratio of 1:1 had the best ammonia decomposition conversion rate at 600°C.

[0068] [Example 29]

[0069] Preparation method of modified Co / Y2O3 catalyst:

[0070] 1. Dissolve 4 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) in a beaker filled with 200 mL of deionized water, add a clean magnetic stir bar to the beaker, place the beaker on a magnetic stirrer, and add 1.9652 g of Y(NO3)3·6H2O and 1.8757 g of Al(NO3)3·9H2O under constant stirring to obtain a mixed solution C;

[0071] 2. After one hour, triethylamine (TEA) was slowly added to the mixed solution C obtained in step 1, and the mixture was stirred continuously until the pH value of the solution was 10. The mixture was then stirred for 4 hours, and aged in a water bath at 90° C. for 3 hours. The mixture was filtered while hot to obtain a white precipitate.

[0072] 3. The white precipitate obtained in step 2 was filtered and washed with deionized water until the filtrate was neutral, and then the white precipitate was placed in a 70°C oven for drying for 12 hours, and then the dried precipitate was placed in a muffle furnace, and the muffle furnace was controlled to heat up to 500°C at a heating rate of 5°C / min and then calcined for 2 hours to obtain a Y2O3-Al2O3 carrier, which was recorded as Y-Al;

[0073] 4. Use an electronic balance to weigh 0.8000g of the above-mentioned carrier and 0.9878g of Co(NO3)2·6H2O respectively, add the weighed Co(NO3)2·6H2O and 15mL of deionized water into a beaker (capacity 100mL), stir until Co(NO3)2·6H2O is dissolved, put a clean magnetic stirring bar and the weighed Y-Al carrier into the beaker, place the beaker on a magnetic stirrer and stir for 3h, then put it into a 60℃ forced drying oven and dry it for 12h, then put the dried product into a muffle furnace, and calcine it at 600℃ for 2h in an air atmosphere at a heating rate of 5℃ / min to obtain the catalyst Co / Y-Al.

[0074] The obtained catalyst contains 80% Y-Al mixed oxide carrier, the content of metal cobalt as active component in the catalyst accounts for 20% by weight, and the specific surface area of ​​the catalyst is 65m 2 / g.

[0075] [Examples 30-35]

[0076] Y(NO3)3·6H2O, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), triethylamine (TEA) and nitrate compound raw materials containing the elements magnesium, lanthanum, zinc, zirconium, aluminum, cerium, iron, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, erbium, thulium, ytterbium, lutetium and scandium are prepared according to the preparation conditions in Table 4 and the steps in Example 29 to obtain the modified catalysts of Examples 30-35.

[0077] Table 5

[0078]

[0079]

[0080] [Examples 36-42] Using modified catalysts to produce hydrogen by decomposing ammonia

[0081] Using ammonia as raw material and the modified catalysts obtained in Examples 29-35, the catalyst performance was evaluated according to the reaction conditions in Table 6.

[0082] Table 6

[0083]

[0084] Finally, it should be emphasized that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a rare earth yttrium oxide-supported cobalt-based catalyst for hydrogen production by ammonia decomposition, characterized in that: The rare earth yttrium oxide supported cobalt-based catalyst comprises the following components in percentage by mass: a) Y2O3 carrier 80% to 95%, the specific surface area of ​​the Y2O3 carrier is 64m 2 / g~80 m 2 / g, b) Transition metal element cobalt 5% to 20%; The preparation method comprises the following steps: 1) Dissolve the surfactant in deionized water and then add Y(NO3)3 under stirring. . 6H2O to obtain a mixed solution A, wherein the surfactant is a triblock copolymer of polyethylene oxide-polypropylene oxide-polyethylene oxide, and the amount of the surfactant is 5-10 mmol, Y(NO3)3 . The amount of 6H2O is 5 to 15 mmol, and the amount of deionized water is 100 to 200 mL; 2) Slowly add triethylamine dropwise to the mixed solution A, then continue stirring for 5 to 12 hours under water bath heating at a temperature of 50 to 100°C, take out and age for 6 to 24 hours, and then filter to obtain a white precipitate; 3) washing the white precipitate obtained in step 2) with deionized water until the filtrate is neutral, drying the white precipitate at a temperature of 60 to 120° C. for 8 to 24 h, and then calcining the precipitate to obtain a Y2O3 carrier at a temperature of 300 to 1000° C.; 4) Co(NO3)2 . 6H2O is dissolved in a solution, which is one or a combination of deionized water, anhydrous ethanol, anhydrous methanol or anhydrous acetone, and then impregnated onto the Y2O3 carrier. After drying, the dried product is calcined in an air atmosphere to obtain the catalyst Co / Y2O3, the drying temperature is 60-120°C, and the calcination temperature is 400-1000°C.

2. A method for preparing a modified yttrium oxide-supported cobalt-based catalyst for hydrogen production by ammonia decomposition, characterized in that: The modified yttrium oxide-supported cobalt-based catalyst comprises the following components in percentage by mass: a) Y2O3-M y O x The carrier is 70% to 95%, M is one of magnesium, lanthanum, zinc and aluminum, and the Y2O3-M y O x The specific surface area of ​​the carrier is 61.3m 2 / g~89m 2 / g, b) Transition metal element cobalt 5% to 30%; The preparation method comprises the following steps: 1) Dissolve the surfactant in deionized water and then add Y(NO3)3 under stirring. . 6H2O and metal salt N to obtain a mixed solution B, the surfactant is a triblock copolymer of polyethylene oxide-polypropylene oxide-polyethylene oxide, the amount of the surfactant is 5-10 mmol, Y(NO3)3 . The amount of 6H2O is 3 to 9 mmol, Y(NO3)3 . The molar ratio of 6H2O to metal salt N is 1:1 to 1:9, the amount of deionized water is 100 to 200 mL, and the metal salt N is one of magnesium nitrate pentahydrate, lanthanum nitrate hexahydrate, zinc acetate, and aluminum nitrate nonahydrate; 2) slowly adding triethylamine dropwise to the mixed solution B obtained in step 1), then continuing stirring for 5 to 12 hours, and aging in a water bath, filtering while hot to obtain a precipitate, the water bath heating temperature is 60 to 120° C., and the aging time is 12 to 24 hours; 3) The precipitate obtained in step 2) is washed with deionized water until the filtrate is neutral, and then the precipitate is dried at a temperature of 60 to 120°C for 8 to 18 hours, and then calcined to obtain Y2O3-M y O x Carrier, calcination temperature is 300~1000℃; 4) Co(NO3)2 . 6H2O is dissolved in a solution, wherein the solution is one or a combination of deionized water, anhydrous ethanol, anhydrous methanol or anhydrous acetone, and then impregnated into the Y2O3-M y O x The carrier is dried and the dried product is calcined in air atmosphere to obtain the catalyst Co / Y2O3-M y O x , the drying temperature is 60-180°C, and the calcination temperature is 300-900°C.

3. Application of cobalt-based catalyst in hydrogen production by decomposition of ammonia, characterized in that: The cobalt-based catalyst is prepared by the preparation method according to claim 1 or claim 2; The cobalt-based catalyst is used in the decomposition of ammonia to produce hydrogen, with ammonia as the raw material, at a reaction temperature of 300 to 600° C., a reaction pressure of normal pressure ± 0.01 MPa, and a weight space velocity of 6000 to 30000 mLh -1 g cat -1 The catalyst is contacted with a high-temperature reactor under the conditions of . In the reactor, the catalyst needs to be reduced with hydrogen before contacting with ammonia. The hydrogen reduction temperature is in the range of 500 to 700 ° C, and the reaction generates nitrogen and hydrogen products.

Citation Information

Patent Citations

  • Rare earth oxide supported ruthenium catalysts, their preparation methods and applications

    CN112774676B